Primary Hyperparathyroidism and Cardiac Arrest: Case report - Mahmood, Omaima; Mahmood, Saeed AG; Mohammed, Zahraa (Indian Journal of Case Reports, 2016)
Hyperparathyroidism is a common endocrine disorder characterized by hypersecretion of parathyroid hormones due to abnormal activity of one or more parathyroid glands. Several cardiac abnormalities have been reported due to hyperparathyroidism. In this case report, a case of cardiac arrest due to hyperparathyroidism and hypercalcemia is presented and discussed. A female patient, 73 years old, was admitted to surgical ward (SICU) with malignant goiter extending to the retrosternum. She was a known case of hyperparathyroidism and hypercalcemia. After the operation, the patient was shifted to SICU for further management. Suddenly, the patient had sudden cardiac arrest and was successfully resuscitated within 2 minutes. The ECG showed a new Right Bundle Branch Block (RBBB) changes. Patient remained on ventilator, not obeying commands, and opened her eyes spontaneously with cough reflex. A week after, percutaneous tracheostomy was performed, and patient became hemodynamically stable, weaned from ventilator and allowed to breathe spontaneously. Although cardiac arrest is a rare complication, it should be expected by health care providers when dealing with patients with hyperparathyroidism and hypercalcemia.